Method for recovering high-density solid phase in waste shale gas oil-based drilling fluid
By employing pretreatment and heavy liquid preparation methods, the problem of recovering high-density solid phases from waste shale gas and oil-based drilling fluids has been solved, achieving efficient separation and recovery, and improving the recovery rate of barite and resource utilization efficiency.
Patent Information
- Application Number
- CN202511267280.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-05
- Publication Date
- 2025-12-12
AI Technical Summary
Existing technologies are insufficient for efficiently recovering high-density solid phases from waste shale gas and oil-based drilling fluids, leading to resource waste and environmental pollution. Furthermore, existing methods suffer from high equipment investment, small processing capacity, and low recovery efficiency.
The process involves pretreatment to break down the gel and dehydrate the product, extraction of the residual oil phase with organic solvent, preparation of a heavy liquid and adjustment of the ratio of potassium iodide and zinc iodide, and separation of high and low density solid phases by shaking and settling to achieve efficient separation and recovery.
The high-density solid phase recovery rate reached 96.6%, with barite accounting for 71.6% of the high-density solid phase. More low-density solid phase was separated, reducing processing costs and improving resource recycling rate.
Smart Images

Figure CN121111147A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of oilfield environmental protection technology, specifically relating to a method for recovering high-density solid phases from waste shale gas and oil-based drilling fluids. Background Technology
[0002] Shale gas, as a crucial component of the global energy transition, relies heavily on the widespread application of oil-based drilling fluids for its efficient development. However, the waste solids generated during shale gas extraction using oil-based drilling fluids have become a key environmental issue hindering the industry's sustainable development. The solids of waste shale gas oil-based drilling fluids primarily consist of barite, bentonite, and other impurities introduced during drilling. Furthermore, due to environmental factors, they contain significant amounts of rock cuttings and rock powder, resulting in a high density and small average particle size.
[0003] Over 85% of my country's barite resources are used as weighting agents in drilling fluids for oil and gas fields, specifically in deep and ultra-deep wells, where the fluid density exceeds 1.8 g / cm³. 3 In high-density waste drilling fluids returned to the surface, where the weighting material accounts for more than 35% of the volume, a large amount of potentially recyclable barite resources remain. Excessive resource consumption, significant waste during extraction, and low recovery quality and efficiency have severely constrained the development of my country's barite industry. Therefore, effective recycling of barite from high-density waste drilling fluids in oil and gas fields is imperative; however, separating it from the waste solid phase remains a challenge.
[0004] Currently, the main methods for recovering barite from waste solids are centrifugation and flotation. However, neither method can achieve optimal recovery results in practice, and both have their limitations. Centrifugation has a relatively complete research system in China, is widely used, and has good recovery results. However, it requires large equipment investment, has a small processing capacity, low recovery efficiency, and only moderate fine particle separation effect. It also has limited capacity for handling high-density drilling fluids and is not suitable for solids with similar densities among different components. Flotation can significantly improve the quality of recovered barite, but currently, there are difficulties in screening targeted flotation agents in China, the mechanism research is not in-depth, there are few case studies for reference, and the technology is immature, making large-scale application difficult.
[0005] Therefore, developing a method for recovering high-density solids from waste shale gas and oil-based drilling fluids is of great significance. Through in-depth research and practical exploration, this method can not only solve the problem of waste oil-based drilling fluid treatment, protecting the ecological environment and human health, but also enable the recycling of barite, reduce drilling costs, and achieve cleaner production. Summary of the Invention
[0006] In order to overcome the shortcomings of the prior art, the main objective of this invention is to provide a method for recovering high-density solid phases from waste shale gas and oil-based drilling fluids, so as to solve the problems of secondary pollution, high energy consumption and environmental pollution in existing treatment methods.
[0007] To achieve the above objectives, the present invention provides the following technical solution: a method for recovering high-density solid phases from waste shale gas and oil-based drilling fluid, comprising the following steps.
[0008] 1) Pretreatment: Dehydrate the waste shale gas and oil-based drilling fluid by breaking it apart, then add an organic solvent to extract the residual oil phase in the solid phase, and collect the remaining solid phase;
[0009] 2) Preparation of heavy liquid: Add potassium iodide to distilled water, stir to dissolve, then add zinc iodide and stir to mix to obtain heavy liquid;
[0010] 3) Separation treatment: Mix the collected solid phase with the heavy liquid at a ratio of 1g: 8-15mL, shake and let stand for 5-8 hours to separate the solid phase with a density greater than that of the heavy liquid.
[0011] Furthermore, in step 1), the dehydration and gel breaking process is as follows:
[0012] First, add 10% to 40% of the waste oil-based drilling fluid by weight of deionized water and stir to dilute. Then, add 0.2% to 1.0% of the waste oil-based drilling fluid by weight of calcium oxide and stir to dissolve. Next, add 2.0% to 8.0% of the waste oil-based drilling fluid by weight of hydrochloric acid and aminosulfonic acid and stir until the reaction is stable. Then, separate the aqueous phase from the gel and the gel breaking is complete.
[0013] Furthermore, in the above-mentioned degelatinization and dehydration steps, the amount of deionized water added is 20% of the mass of the waste oil-based drilling fluid, the amount of calcium oxide added is 0.6% of the mass of the waste oil-based drilling fluid, and the amount of hydrochloric acid and aminosulfonic acid added is 5.0% of the mass of the waste oil-based drilling fluid.
[0014] Furthermore, the mass ratio of hydrochloric acid to aminosulfonic acid is 0-2:1-3.
[0015] Furthermore, in step 1), the organic solvent is one or more of petroleum ether, toluene, and xylene;
[0016] Furthermore, in step 1), the mass ratio of the drilling fluid to petroleum ether is 1:1 to 4.
[0017] Furthermore, in step 1), after the oil phase is extracted, the remaining solid phase is dried in an oven at 100°C for 120 minutes.
[0018] Furthermore, in step 2), the temperature of the heavy liquid is 20–60°C, preferably 30–50°C;
[0019] Furthermore, in step 2), the mass ratio of distilled water, zinc iodide, and potassium iodide is 1:2 to 4:1 to 2;
[0020] Furthermore, in step 3), the settling time is 6 hours.
[0021] Furthermore, the density of the heavy liquid is controlled between 2.00 and 3.00 g / cm³ by adjusting the ZnI₂ / KI ratio. 3 .
[0022] Compared with existing technologies, the above-mentioned technical solution has the following advantages in recovering high-density solid phases from waste shale gas and oil-based drilling fluids:
[0023] 1. The heavy liquid prepared in this invention uses a mixed salt solution, which overcomes the solubility limitation of a single salt through the complexation effect. By adjusting the ratio of potassium iodide and zinc iodide, the density of the heavy liquid can be precisely controlled, solving the problem of the narrow density range of a single heavy liquid and achieving higher density and stronger coordination ability.
[0024] 2. The heavy liquid prepared in this invention uses potassium iodide to neutralize the acidity of zinc iodide, thus expanding the applicable pH range of the solution.
[0025] 3. The heavy liquid preparation of this invention is simple and quick, the processing technology is simple, the operation is strong, and the processing cost is low, making it suitable for the treatment of solid phases of waste drilling fluid.
[0026] 4. The recovery rate of the high-density solid phase of this invention can reach 96.6%, with barite accounting for 71.6% of the high-density solid phase. More low-density solid phase is separated, making it easier to recover and reuse it as a weighting agent in drilling fluid. Attached Figure Description
[0027] Figure 1 The barium sulfate characteristic peak information is shown in the XRD pattern of the solid sample obtained in Example 1 of this invention.
[0028] Figure 2 This is the silica characteristic peak information of the XRD spectrum of the solid sample obtained in Example 1 of the present invention. Detailed Implementation
[0029] The present invention will now be described in detail with reference to specific embodiments.
[0030] The present invention will now be described in detail with reference to specific embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention. These all fall within the scope of protection of the present invention.
[0031] Example 1: Pretreatment of waste shale gas and oil-based drilling fluid
[0032] A certain amount of waste shale gas-oil-based drilling fluid was weighed. The waste oil-based drilling fluid had a water content of 32%, a solid content of 57%, and an oil content of 11%.
[0033] First, add 20% deionized water (by weight of the waste oil-based drilling fluid) and stir to dilute. Then, add 0.6% calcium oxide (by weight of the waste oil-based drilling fluid) and stir to dissolve. Next, add 5.0% hydrochloric acid and aminosulfonic acid (by weight of the waste oil-based drilling fluid), with a mass ratio of 1:2. Stir for 7.5 minutes until the reaction stabilizes. Then, separate the aqueous phase from the gel. The gelled waste oil-based drilling fluid will then proceed to the next step of processing.
[0034] Waste oil-based drilling fluid, after gelation and separation of the aqueous phase, was placed in a stoppered graduated cylinder. Petroleum ether was then added and shaken to mix. The drilling fluid and petroleum ether were added at a mass ratio of 1:2. The stoppered graduated cylinder, after initial shaking, was then placed in a water bath and heated at 40°C for 30 minutes, shaking every 10 minutes during this period. The heated sample was then poured into centrifuge tubes and centrifuged at 3000 rpm for 10 minutes. After centrifugation, the upper solvent layer and the lower solid phase were separated. The lower solid phase, after the oil phase was removed, was collected and placed in an oven to dry the residual petroleum ether, yielding a solid sample for later use.
[0035] Example 2: Preparation of heavy liquid
[0036] Add 100mL of distilled water to a beaker and place it in a constant temperature water bath. After the temperature rises to 30℃, add 150g of KI in batches and stir until completely dissolved to form a transparent solution. Then, slowly add 250g of ZnI2 in several batches, adding a small amount each time after it dissolves, while continuing to stir until a small amount of insoluble matter appears in the solution. Finally, maintain the temperature and continue stirring for 10-15 minutes to ensure dissolution equilibrium.
[0037] Using a preheated funnel, filter the solution while it is still hot to remove undissolved solute, obtaining a clear, saturated solution. Then, cool the filtrate to room temperature to obtain a saturated ZnI₂-KI system solution. The density of the system solution was measured to be approximately 2.52 g / cm³. 3 .
[0038] Example 3: Preparation of heavy liquid
[0039] Add 100mL of distilled water to a beaker and place it in a constant temperature water bath. After the temperature rises to 40℃, add 150g of KI in batches and stir until completely dissolved to form a transparent solution. Then, slowly add 300g of ZnI2 in several batches, adding a small amount each time after it dissolves, while continuing to stir until a small amount of insoluble matter appears in the solution. Finally, maintain the temperature and continue stirring for 10-15 minutes to ensure dissolution equilibrium.
[0040] Using a preheated funnel, filter the solution while it is still hot to remove undissolved solute, obtaining a clear, saturated solution. Then, cool the filtrate to room temperature to obtain a saturated ZnI₂-KI system solution. The density of the system solution was measured to be 2.67 g / cm³. 3 .
[0041] Example 4: Preparation of heavy liquid
[0042] Add 100mL of distilled water to a beaker and place it in a constant temperature water bath. After the temperature rises to 50℃, add 150g of KI in batches and stir until completely dissolved to form a transparent solution. Then, slowly add 350g of ZnI2 in several batches, adding a small amount each time after it dissolves, while continuing to stir until a small amount of insoluble matter appears in the solution. Finally, maintain the temperature and continue stirring for 10-15 minutes to ensure dissolution equilibrium.
[0043] Using a preheated funnel, filter the solution while it is still hot to remove undissolved solute, obtaining a clear, saturated solution. Then, cool the filtrate to room temperature to obtain a saturated ZnI₂-KI system solution. The density of the system solution was measured to be 2.79 g / cm³. 3 .
[0044] Example 5: Separation Process
[0045] Take 10g of the treated solid phase and place it in a 250mL stoppered graduated cylinder. Add 100mL of a prepared solution with a density of 2.52g / cm³. 3 The heavy liquid was agitated 100 times (amplitude greater than 5 cm), then agitated once every ten minutes for a total of 3 times. Afterward, it was placed on a fixed rack and allowed to stand for 6 hours. Once separation was complete, the upper and lower solid phases of the heavy liquid were separated; the lower phase had a density greater than 2.52 g / cm³. 3 The solid phase mass is 6.34 g, and the density at the top is less than 2.52 g / cm³. 3 The solid phase mass is 3.12 g.
[0046] High-density solids accounted for 81.5% of the recovered solids, and barite accounted for 60.4% of the recovered solids.
[0047] Example 6: Separation Process
[0048] Take 10g of the treated solid phase and place it in a 250mL stoppered graduated cylinder. Add 100mL of a prepared solution with a density of 2.67g / cm³. 3 The heavy liquid was agitated 100 times (amplitude greater than 5 cm), then agitated once every ten minutes for a total of 3 times. Afterward, it was placed on a fixed rack and allowed to stand for 6 hours. Once separation was complete, the upper and lower solid phases of the heavy liquid were separated; the lower phase had a density greater than 2.67 g / cm³. 3 The solid phase mass is 6.26 g, and the density at the top is less than 2.67 g / cm³. 3 The solid phase mass is 3.24 g.
[0049] High-density solids accounted for 82.6% of the recovered solids, and barite accounted for 61.2%.
[0050] Example 7: Separation Process
[0051] Take 10g of the treated solid phase and place it in a 250mL stoppered graduated cylinder. Add 100mL of a prepared solution with a density of 2.79g / cm³. 3 The heavy liquid was agitated 100 times (amplitude greater than 5 cm), then agitated once every ten minutes for a total of 3 times. Afterward, it was placed on a fixed rack and allowed to stand for 6 hours. Once separation was complete, the upper and lower solid phases of the heavy liquid were separated; the lower phase had a density greater than 2.79 g / cm³. 3 The solid phase mass is 5.35 g, and the density at the top is less than 2.79 g / cm³. 3 The solid phase mass is 4.27 g.
[0052] High-density solids accounted for 96.6% of the recovered solids, and barite accounted for 71.6% of the high-density solids.
[0053] Comparative Example 1
[0054] Take 10g of the treated solid phase and place it in a 250mL stoppered graduated cylinder. Add 100mL of a prepared solution with a density of 2.79g / cm³. 3 The heavy liquid was agitated 100 times (amplitude greater than 5 cm), then agitated once every ten minutes for a total of 3 times. Afterward, it was placed on a fixed rack and allowed to stand for 4 hours. Once separation was complete, the upper and lower solid phases of the heavy liquid were separated; the lower phase had a density greater than 2.79 g / cm³. 3 The solid phase mass is 4.92 g, and the density at the top is less than 2.79 g / cm³. 3 The solid phase mass is 3.67g. Since it did not settle completely, approximately 1.41g of suspended particles are calculated to remain in the heavy liquid.
[0055] Comparative Example 2
[0056] Take 10g of the treated solid phase and place it in a 250mL stoppered graduated cylinder. Add 100mL of a prepared solution with a density of 2.79g / cm³.3 The heavy liquid was agitated 100 times (amplitude greater than 5 cm), then agitated once every ten minutes for a total of 3 times. Afterward, it was placed on a fixed rack and allowed to stand for 8 hours. Once separation was complete, the upper and lower solid phases of the heavy liquid were separated; the lower phase had a density greater than 2.79 g / cm³. 3 The solid phase mass is 5.42 g, and the density at the top is less than 2.79 g / cm³. 3 The solid phase mass is 4.35g. After complete sedimentation, it is calculated that there are still approximately 0.23g of suspended particles in the heavy liquid.
[0057] As can be seen from Examples 7, 1, and 2, 4 hours only allowed some high-density particles to settle and some low-density particles to float. However, the remaining finer particles were still in the process of slow settling and floating, and complete separation was not achieved, resulting in a large number of particles in the intermediate heavy liquid and poor separation effect. By 6 hours, most particles had completely settled and floated, and there were no obvious suspended particles in the heavy liquid. After 8 hours of settling, the suspended particles in the heavy liquid decreased by only 0.13 g. The separation of these particles had little impact on the overall recovery rate and required an additional 2 hours. Based on the experimental data from the three sets, a settling time of 6 hours was determined to ensure the separation rate of high and low density solid phases while avoiding wasted time.
[0058] Comparative Example 3
[0059] This comparative method for recovering high-density solid phases from waste shale gas-oil-based drilling fluid follows the same steps as in Example 1, except that in step 1), the waste shale gas-oil-based drilling fluid degelatinization and dehydration process is performed without adding deionized water for stirring and dilution. Instead, 0.6% (by weight) of calcium oxide from the waste oil-based drilling fluid is directly added and stirred to dissolve it. Then, 5.0% (by weight) of hydrochloric acid and aminosulfonic acid from the waste oil-based drilling fluid are added, with a mass ratio of hydrochloric acid to aminosulfonic acid of 1:2. The stirring time is 7.5 minutes. After the reaction stabilizes, the aqueous phase from the degelatinization process is separated, and the degelatinized waste oil-based drilling fluid is then processed in the next step.
[0060] Failing to dilute with deionized water leads to a decrease in both high-density solids recovery and barite recovery. Waste shale gas and oil-based drilling fluids are characterized by high viscosity and dense solid-liquid distribution. Without dilution, the reagents will locally aggregate, failing to fully contact the drilling fluid colloids, resulting in incomplete gel breaking reaction. The subsequently collected solids will still contain a large amount of water. Furthermore, due to incomplete gel breaking, the oil phase remains tightly adhered to the solids, making it difficult for organic solvents to penetrate to the oil-solid interface and effectively extract residual oil. The high residual oil content in the solids causes particle agglomeration, causing fine barite particles to adhere to low-density impurities and float to the surface, thus reducing barite recovery. On the other hand, without dilution, some unreacted reagents cannot be separated from the aqueous phase due to the system's viscosity, ultimately mixing into the collected solids, leading to a more complex solids composition and reducing subsequent high-density solids recovery.
[0061] The solid phase obtained from the pretreatment in Example 1 was analyzed using X-ray fluorescence spectrometry (XRF), and the content of each element in the solid phase is shown in the table below:
[0062] Table 1. Solid-phase XRF obtained in Example 1
[0063] Molecular formula content(%) <![CDATA[SiO2]]> 30.48 BaO 23.7 <![CDATA[SO3]]> 14.59 CaO 8.815 <![CDATA[Fe2O3]]> 7.411 <![CDATA[Al2O3]]> 6.017 NaCl 2.631 <![CDATA[Cr2O3]]> 2.265 MgO 1.85 <![CDATA[K2O]]> 1.07
[0064] Elemental composition analysis of the solid phase obtained from the pretreatment in Example 1 was performed using X-ray fluorescence spectrometry (XRF). Table 1 shows that the main elements in the solid phase obtained after three-phase separation are silicon (Si), barium (Ba), sulfur (S), calcium (Ca), iron (Fe), and aluminum (Al), with SiO2 being the most abundant. This is because the formation contains a high proportion of silicate minerals (quartz, feldspar, and clay), which is consistent with the basic logic of drilling fluid carrying formation debris. The high content of BaO may correspond to barite residues, while SO3 is the result of sulfate in barite calculated as SO3. Al2O3 comes from clay minerals (such as kaolinite and montmorillonite), CaO comes from carbonate rocks (calcite and dolomite) or feldspar minerals, and Fe2O3 is a common impurity element in the formation. It can be seen that the solid phase obtained after separation may contain a high amount of barite.
[0065] from Figure 1 and Figure 2 The image shows the solid phase XRD pattern obtained after pretreatment in Example 1. The XRD pattern shows that silicon (Si), barium (Ba), and sulfur (S) in the solid phase obtained after three-phase separation are mainly present in the form of silicon dioxide and barium sulfate. This verifies that Si appears in the XRF pattern as silicon dioxide, while BaO and SO3 appear in the form of barite (theoretically, BaO accounts for approximately 65.7% and SO3 approximately 34.3% in barite BaSO4; in this data, the ratio of BaO (23.7%) to SO3 (14.59%) is approximately 1.6:1, close to the theoretical value of 1.9:1, further verifying that SO3 comes from barite, not other sulfates). This indicates that there is a large amount of barite in the solid phase that has not been lost with the liquid phase, possessing good recovery value. The high-density solid phase can be separated using sorting technology, and the purified barite can be reused as a weighting agent in drilling fluids.
[0066] Figure 1 and Figure 2Both figures show solid-state XRD patterns. The diffraction peak markers below the curves do not overlap, corresponding to the diffraction peak positions of their respective phases within the solid phase. Due to the differences in atomic density and arrangement symmetry between different crystal planes in the two phases, the diffraction intensities of each plane differ significantly, resulting in characteristic diffraction peaks appearing at different angles. Furthermore, in addition to the diffraction peaks corresponding to the markers for barium sulfate and silicon dioxide, the XRD patterns show extra diffraction peaks, indicating that the treated solid-state system contains multiple other phases besides the target component, making the overall system composition quite complex.
[0067] The specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the specific embodiments described above, and those skilled in the art can make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for recovering high-density solid phase from waste shale gas and oil-based drilling fluid, characterized in that: Includes the following steps, 1) Pretreatment: Dehydrate the waste shale gas and oil-based drilling fluid by breaking it apart, then add an organic solvent to extract the residual oil phase in the solid phase, and collect the remaining solid phase; 2) Preparation of heavy liquid: Add potassium iodide to distilled water, stir to dissolve, then add zinc iodide and stir to mix to obtain heavy liquid; 3) Separation treatment: Mix the collected solid phase with the heavy liquid at a ratio of 1g: 8-15mL, shake and let stand for 5-8 hours to separate the solid phase with a density greater than that of the heavy liquid.
2. The method for recovering high-density solid phase from waste shale gas and oil-based drilling fluid according to claim 1, characterized in that: In step 1), the dehydration and gel breaking process is as follows: First, add 10% to 40% of the waste oil-based drilling fluid by weight of deionized water and stir to dilute. Then, add 0.2% to 1.0% of the waste oil-based drilling fluid by weight of calcium oxide and stir to dissolve. Next, add 2.0% to 8.0% of the waste oil-based drilling fluid by weight of hydrochloric acid and aminosulfonic acid and stir until the reaction is stable. Then, separate the aqueous phase from the gel and the gel breaking is complete.
3. The method for recovering high-density solid phase from waste shale gas and oil-based drilling fluid according to claim 2, characterized in that: The amount of deionized water added is 20% of the mass of the waste oil-based drilling fluid, the amount of calcium oxide added is 0.6% of the mass of the waste oil-based drilling fluid, and the amount of hydrochloric acid and aminosulfonic acid added is 5.0% of the mass of the waste oil-based drilling fluid.
4. A method for recovering high-density solid phase from waste shale gas and oil-based drilling fluid according to any one of claims 2-3, characterized in that: The mass ratio of hydrochloric acid to aminosulfonic acid is 0-2:1-3.
5. The method for recovering high-density solid phase from waste shale gas and oil-based drilling fluid according to claim 1, characterized in that: In step 1), the organic solvent is one or more of petroleum ether, toluene, and xylene.
6. The method for recovering high-density solid phase from waste shale gas and oil-based drilling fluid according to claim 1, characterized in that: In step 1), the mass ratio of drilling fluid to petroleum ether is 1:1 to 4.
7. The method for recovering high-density solid phase from waste shale gas and oil-based drilling fluid according to claim 1, characterized in that: In step 1), after the oil phase is extracted, the remaining solid phase is dried in an oven at 100°C for 120 minutes.
8. The method for recovering high-density solid phase from waste shale gas and oil-based drilling fluid according to claim 1, characterized in that: In step 2), the temperature of the heavy liquid is 20-60°C, preferably 30-50°C.
9. The method for recovering high-density solid phase from waste shale gas and oil-based drilling fluid according to claim 1, characterized in that: In step 2), the mass ratio of distilled water, zinc iodide, and potassium iodide is 1:2 to 4:1 to 2; in step 3), the standing time is 6 hours.
10. The method for recovering high-density solid phase from waste shale gas and oil-based drilling fluid according to claim 9, characterized in that: The density of the heavy liquid was controlled between 2.00 and 3.00 g / cm³ by adjusting the ZnI₂ / KI ratio. 3 .